Development of Thai Y series fan culture in China - Li, Lanxin; Jutaviriya, Keeratiporn; Boonwanna, Thananan (Thai Journal of East Asian Studies, 2024)
This research article aims to study the development of Thai Y series fan culture in China. Employing a documentary research approach within the framework of fan culture theories, this study draws upon content analysis sourced from the discourse of Chinese fans on the Weibo platform. The findings reveal three distinct phases in the development of Thai Y series fan culture in China. Phase 1 (2014-2018): Chinese fans relied on subtitle groups to access and engage with Thai Y series. However, faced with copyright constraints, Chinese fans adapted their viewing practices by accessing Y-Thai series content via cloud drives in conjunction with subtitle groups. Phase 2 (2019-2021): The blossoming growth of Thai Y series and widespread popularity in China. As Thai Y series gained mainstream recognition in China, fans became increasingly interested in the symbolic and identity-related benefits associated with consuming products related to their favorite artists, rather than the practical use of these products. Phase 3 (2022-present): Diversity in the fan culture of Thai Y series. In recent years, Chinese fans have gained greater opportunities to interact with Thai Y series artists. This has led to an increase in transnational business value, benefiting both the Thai Y series artists and their devoted fans. Additionally, fans are increasingly being incorporated into the production and marketing of Thai Y series, as well as creating a fan culture in business that connects with other countries in the Mekong Basin.